Sistem Pengelolaan Kebijakan Publik di Kerajaan Cirebon - Augustina Rina Herawati (Lembaga Administrasi Negara, 2017)
Public Policy is a binding decision for the people at the strategic or outline level created by the public authority. The Sultanate of Cirebon was a prominent Islamic sultanate in West Java in the 15thand 16thcenturies, and was an important base in the inter-island trade and shipping routes. Public policy management system in Cirebon Kingdom covers politics, religion, and economic, socio-culture. Political, religious, economic, socio-cultural policy, implemented in the Kingdom of Cirebon has proven to increase the development of the kingdom. This study is a combined descriptive and development studies. It is found that good governance in the area can be adopted in NKRI. So it is necessary to consider the formulation of policy by using socio-cultural approach for both culture.Keywords: cirebon kingdom, public policy, public authority